Microstructure and mechanical properties of directionally solidified Mg–Zn alloy as a biomaterial. Issue 18 (12th December 2019) - Jia, Hongmin; Feng, Xiaohui; Yang, Yuansheng
ABSTRACT: Directionally solidified Mg-4wt-% Zn alloy was prepared and the effect of growth rate on its microstructure evolution and mechanical properties was investigated. A typical cellular structure was observed when the growth rate was lower than 60 µm s −1 . The microstructure evolved from cell to columnar dendrite as the growth rate increased. The ultimate tensile strength of the directionally solidified alloy was found to be higher than that of the alloy ingot with the same cooling rate. The ultimate tensile strength of the directionally solidified alloy increased with increasing growth rate but it decreased during the cell–dendrite transition. The results indicate that the mechanical properties of the directionally solidified alloy with fine cellular and columnar dendritic structures meet the requirements of biomaterials.